Is There Visceral Adipose Tissue (VAT) Intracellular Hypercortisolism in Human Obesity? - Alfonso, B.; Araki, T.; Zumoff, B. (Hormone and Metabolic Research, 2013)
The fact that obesity is a prominent feature of Cushing’s syndrome (systemic hypercortisolism of adrenocortical origin) stimulated a 40-year search for evidence of systemic hypercortisolism in human obesity. That search has failed to find such evidence. For the past 15 years, however, studies have been done to evaluate a possible alternative type of hypercortisolism in obesity, namely visceral adipose tissue (VAT) intracellular hypercortisolism. The current review summarizes the evidence published so far about this possibility. There have been three types of evidence studied: direct measurement of the VAT levels of 11β-hydroxysteroid dehydrogenase type I (11-HSD-1), which converts biologically inactive cortisone to biologically active cortisol; direct measurement of splanchnic cortisol production; and evaluation of the effect of a specific inhibitor of 11-HSD-1 on metabolic abnormalities associated with obesity, particularly diabetes mellitus. The results are complex and difficult to interpret. Our conclusion is that the presence of VAT intracellular hypercortisolism in human obesity is possible but unlikely.
Keywords: obesity; intracellular cortisol production; 11β-hydroxysteroid dehydrogenase